HUBUNGAN ANTARA INKOMPTABILITAS ABO, FREKUENSI PEMBERIAN ASI DAN SUMBER INFORMASI IBU POSTPARTUM TERHADAP KEJADIAN HIPERBILIRUBIN PADA BAYI BARU LAHIR - Ageng Septa Rini; Pramita Kencana Mahareny; Stefanus Eke Ola (Poltekkes Kemenkes Maluku, 2021)
Hyperbilirubinemia is common condition in newborns which refers to yellow color of skin and sclera on the eyes due to much bilirubin in the blood, where jaundice is one of most common emergencies in newborns. This study aims to determine the relationship between ABO Incompatibility, Frequency of Breastfeeding and Information Sources for Post Partum Mothers on the Incidence of Hyperbilirubinemia. Quantitative research design using descriptive analytic method with a cross sectional approach. The population in this study were all post partum mothers who had babies with hyperbilirubinemia at Zahirah Jagakarsa General Hospital, South Jakarta. The sample of this study used the Total Sampling technique. The research data showed that there was a relationship between ABO incompatibility with the incidence of hyperbilirubinemia where the p value = 0.003 with OR value of 4.0, there was a relationship between the frequency of breastfeeding and the incidence of hyperbilirubinemia where p value = 0.033 with OR of 2.3, there was a relationship between Source Information on Post Partum Mother with Hyperbilirubin Incidence where p value = 0.045 with OR 2.1. Therefore, the hospital also advised to improve the quality of service through socialization about hyperbilirubin, so that mothers who have the potential to have babies with hyperbilirubinemia can obtain accurate information and can reduce anxiety and risk of hyperbilirubinemia their babies.